PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR IPA KELAS V TEMA 8 MATERI SIKLUS AIR DI MI MIFTAHUL ULUM PANDANARUM - Fadilah Rohmah; Fauzi, Akhmad (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2024)
The decrease in the average PISA score in the field of science from 403 in 2015 to 396 in 2018 shows a decrease in science learning in Indonesia. Similarly, grade V students at MI Miftahul Ulum Pandanarum experience difficulties in science subjects, with 50% of students not meeting KKM and an average PAS score of 45. Lack of student enthusiasm for material that is considered difficult and boring and limitations in the learning model used., The purpose of this study was to determine the influence and how much influence the use of the Team Games Tounament (TGT) Type Cooperative Learning Model on Science Learning Outcomes Theme 8 Water Cycle Material at MI Miftahul Ulum Pandanarum. The type of research used is quantitative with a pre-experimental design method, namely one group pretestI-posttest experiment. The research sample used was class V Al-Hakam totaling 29 students with the data collection technique used was a written test (question), The results of the data analysis test explained that there was an increase after the treatment using the TGT model of 52.41, the value = 0.367 for n = 29, then it can be stated = 52.41 > = 0.376. So it can be concluded that, rejected and accepted. And the N-Gain test score with a value obtained 77,1251 or equal to 77% is an effective criterion, so it can be stated that there is an influence and there is a big influence of the Team Games Tounament (TGT) Type Cooperative Learning Model on Science Learning Outcomes Theme 8 Water Cycle Material at MI Miftahul Ulum Pandanarum.